2021
DOI: 10.4103/2221-1691.311754
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of rice bran hydrolysates on heart rate variability, cardiac oxidative stress, and cardiac remodeling in high fat and high fructose diet-fed rats

Abstract: Objective: To examine the ameliorative effect of rice bran hydrolysates (RBH) on metabolic disorders, cardiac oxidative stress, heart rate variability (HRV), and cardiac structural changes in high fat and high fructose (HFHF)-fed rats. Methods: Male Sprague-Dawley rats were daily fed either standard chow diet with tap water or an HFHF diet with 10% fructose in drinking water over 16 weeks. RBH (500 and 1 000 mg/kg/day) was orally administered to the HFH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
1
5
2
Order By: Relevance
“…In this study, neither HRV nor BP variables were statistically significantly improved in either the RBO or RRBO groups, although previous studies have reported that supplementation with rice bran and its antioxidant compounds phenols and anthocyanin enhanced HRV by reducing sympathetic activity, restoring sympathovagal balance, and alleviating vagal nerve inflammation ( Bruno and Ghiadoni, 2018 ; Behl et al, 2021 ; Senaphan et al, 2021 ). Senaphan et al (2021) , in their study on rats fed a high-fat and high-fructose diet, demonstrated that rice bran hydrolysates restored HRV by reducing the low frequency/high frequency ratio and improved blood lipids, insulin sensitivity, hemodynamic variables, cardiac oxidative stress, and cardiac structural changes. Typically, in addition to the cardiac autonomic nervous system, BP control is associated with several influencing factors, including baroreflex sensitivity, endothelial function, and the renin-angiotensin system ( Asemu et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 81%
“…In this study, neither HRV nor BP variables were statistically significantly improved in either the RBO or RRBO groups, although previous studies have reported that supplementation with rice bran and its antioxidant compounds phenols and anthocyanin enhanced HRV by reducing sympathetic activity, restoring sympathovagal balance, and alleviating vagal nerve inflammation ( Bruno and Ghiadoni, 2018 ; Behl et al, 2021 ; Senaphan et al, 2021 ). Senaphan et al (2021) , in their study on rats fed a high-fat and high-fructose diet, demonstrated that rice bran hydrolysates restored HRV by reducing the low frequency/high frequency ratio and improved blood lipids, insulin sensitivity, hemodynamic variables, cardiac oxidative stress, and cardiac structural changes. Typically, in addition to the cardiac autonomic nervous system, BP control is associated with several influencing factors, including baroreflex sensitivity, endothelial function, and the renin-angiotensin system ( Asemu et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 81%
“…In this study, we did not observe any statistically signi cant improvement in either HRV or BP outcomes in either the RBO or RRBO groups, although previous studies have reported that supplementation with rice bran and its antioxidant compounds, phenols and anthocyanin, improved HRV by reducing sympathetic activity, reestablishing sympathovagal balance, and alleviating vagal nerve in ammation [16,52,53]. A study by Senaphan et al [53] in rats fed a high fat, high fructose diet showed that rice bran hydrolysates restored HRV by decreasing the LF/HF ratio and improved lipid pro les, insulin sensitivity, hemodynamic parameters, cardiac oxidative stress (decreased MDA and protein carbonyl, upregulated eNOS expression, and increased catalase activity), and cardiac structural changes (reduced cardiac hypertrophy and myocardial brosis).…”
Section: Discussioncontrasting
confidence: 69%
“…RBH was obtained from the faculty of Agro-Industry, Chiang Mai University (Chiang Mai, Thailand). RBH preparation is described in a previous study [ 38 ]. The composition of RBH was: protein content: 27.47% (wet basis), fat: 3.45%, and moisture: 1.44%.…”
Section: Methodsmentioning
confidence: 99%
“…During the 30 days of the supplement, all dogs in this RBH supplemented group were given 500 mg/kg of RBH mixed with a meal per day. The doses of RBH were chosen based on the results of preliminary observations and previous studies [ 37 , 38 ]. BW was measured every week and the RBH supplement dose was adjusted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation